Penyelesaian Sengketa Penyalahgunaan Keadaan dalam Perjanjian Kawin: Antara Wanprestasi dan Perbuatan Melawan Hukum dalam Putusan No 3/Pdt./2015/PN.Sos - Silalahi, Riovaldi Paruntungan; Sembiring, Nirindah Daniella; Putri, Nabila Aulia Adek; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2025)
This research discusses a case of misuse of circumstances (misbruik van omstandigheden) in an agreement, as occurred in District Court Decision Number 3/Pdt./2015/PN.Sos between Rugaya Hadadi (Plaintiff) and Achmad Zulfikar (Defendant). This study aims to analyze the judge's consideration in deciding the case as well as the legal consequences of the cancellation of the agreement due to misuse of circumstances. Using normative juridical research methods, the results show that this case is not a default, but a form of misuse of circumstances that causes the agreement to be canceled. The legal consequences of canceling the agreement are the restoration of the injured party's right to file a claim for compensation and the obligation of the party who has received the performance to return it. These findings emphasize the importance of the role of judges in assessing the validity of an agreement based on the principles of freedom of contract and good faith in order to prevent injustice in the practice of agreement law in Indonesia.